2013
DOI: 10.5578/mb.5033
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Presence of New Delhi Metallo-Beta-Lactamase-1 (NDM-1) by PCR in Carbapenem-Resistant Gram-Negative Isolates

Abstract: Bacteria producing New Delhi metallo-beta-lactamase-1 (NDM-1) exhibit high level resistance to beta-lactams including carbapenems. This broad-spectrum resistance limits treatment options for infections caused by NDM-1 producers. NDM-1 was first isolated from an Indian patient in Sweden; since then, NDM-1 producing isolates have been identified in many countries including Turkey. In this study, we investigated the presence of NDM-1 by PCR method in various gram-negative isolates recovered from clinical specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Currently, a NDM-1 positive K. pneumoniae epidemic was described in a tertiary hospital and 2 of the isolates also harbored the blaOXA-48 (36). Parallel to the results of Turkey, the emergence of NDM-1 producers among K. pneumonae and other Enterobacteriaceae members is reported worldwide, especially from India and Middle East and Far East countries (37,38). Verona integron-encoded MBLs and IMPs are the most common MBLs worldwide especially in Greece, Taiwan, and Japan.…”
Section: Discussionmentioning
confidence: 83%
“…Currently, a NDM-1 positive K. pneumoniae epidemic was described in a tertiary hospital and 2 of the isolates also harbored the blaOXA-48 (36). Parallel to the results of Turkey, the emergence of NDM-1 producers among K. pneumonae and other Enterobacteriaceae members is reported worldwide, especially from India and Middle East and Far East countries (37,38). Verona integron-encoded MBLs and IMPs are the most common MBLs worldwide especially in Greece, Taiwan, and Japan.…”
Section: Discussionmentioning
confidence: 83%
“…MBL E-test was found positive for 78.64% (81), followed by CDST in 54.6% (71), DDST in 53.8% (70), and MHT in 39.2% (51) Table 2. Among 91 Citrobacter koseri tested, carbapenem resistance was detected in 79.1% (72) isolates MBL E-test found positive for 52.74% (48) isolates, followed by CDST in 47.3% (43), DDST in 46.15% (42) and MHT in 28.57% (26) [Table 3].…”
Section: Resultsmentioning
confidence: 99%
“…Their lower frequency might be due to the sample size and geographical region or to timing of the studies as the prevalence of these resistance genes in increasing with time. [ 30 41 ] Emergence of bla NDM-1 producing Citrobacter isolates reported from Bangladesh,[ 42 ] Turkey,[ 43 ] Thailand,[ 44 ] France,[ 45 ] South Africa,[ 46 ] United Arab Emirates,[ 47 ] Canada,[ 48 49 ] and India. [ 50 ] We detected presence of bla NDM-1 in 55.30% (99/179) while bla VIM was present in 17.87% (32/179) of carbapenem resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, molecular studies focusing on carbapenem resistance mechanisms are limited [ 8 , 12 ]. Some regional studies have shown an association between the OXA-48 gene and carbapenem resistance in gram-negative enteric bacilli [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…From this isolated case, NDM-1 was identified as the first resistance gene detected from an international origin [ 14 ]. Yanik et al [ 12 ] conducted a study in Samsun-Turkey in which the carbapenemase enzyme was detected using the MHT technique in gram-negative strains resistant to at least one of the antibiotics (imipenem, meropenem or doripenem). PCR was performed to detect NDM-1, but no NDM-1 gene resistance was found in any of the 210 clinical isolates.…”
Section: Discussionmentioning
confidence: 99%